Kiribati : 2011 Article IV Consultation-Staff Report, Informational Annexes, Debt Sustainability Analysis, Public Information Notice on the Executive Board Discussion, and Statement by the Executive Director for Kiribati. (IMF Staff Country Reports; Country Report, 2011)
The staff report highlights that the economy of Kiribati showed resilience from the global crisis owing to infrastructure projects financed by foreign assistance. Executive Directors stressed the importance of preserving real per capita value of the Revenue Equalization Reserve Fund to ensure fiscal sustainability and intergenerational fairness. They appreciated the multiyear budget framework, which helped in designing realistic fiscal plans. Directors noted the joint IMF-World Bank debt sustainability analysis and encouraged authorities to secure grant financing to support the country's development needs.